Implementasi Kebijakan Peraturan Pangulu Nomor 01 Tahun 2021 Tentang Bantuan Langsung Tunai di Desa Saran Padang - Lestari, Weni Dian; Hartono, Budi; Simamora, Beltah Mamero (Universitas Medan Area, 2024)
Direct Cash Transfer (BLT) in Saran Padang Village, Dolok Silau District, Simalungun Regency, faces several problems, such as poor households that do not receive BLT and delays in disbursing funds for recipients who meet the requirements. This study aims to identify inhibiting factors and analyze the Implementation of Pangulu Regulation Policy Number 01 of 2021 concerning BLT in Saran Padang Village. The method used is a qualitative descriptive approach with data collection techniques according to the theory of George C. Edward III, through observation, interviews, documentation, and data triangulation. The results showed that policy implementation still faces obstacles in communication consistency and uneven distribution of BLT, accompanied by limited budget resources. As a result, the implementation of Pangulu Regulation Policy Number 01 of 2021 concerning BLT in Saran Padang Village has not reached its maximum potential. Suggestions include the need for village deliberations between the village government and the community to establish beneficiary criteria and re-verify prospective BLT beneficiaries.